The Effect of Problem-Based Learning Supported by Interactive Media on Students' Physics Learning Outcomes - Juis Hildayanti; Kosim Kosim; Gunawan Gunawan (Indonesian Journal of STEM Education, 2025)
This study aims to investigate the effect of a Problem-Based Learning (PBL) model supported by interactive media on students' physics learning outcomes. This research employed a quasi-experimental method with a pretest-posttest control group design. The population comprised all Grade 11 Mathematics and Natural Sciences (XI MIPA) students at SMAN 1 Sambelia. A total of 69 students were selected via purposive sampling, consisting of Class XI MIPA 1 (N=34) as the experimental group and Class XI MIPA 2 (N=35) as the control group. Data were collected using a cognitive learning outcome instrument consisting of 20 multiple-choice items. Prior to data collection, the instrument underwent validity, reliability, difficulty index, and discrimination power testing, resulting in 16 valid items used for assessment. The results indicated that the mean score of students taught using the PBL model supported by interactive media was 77.50, whereas the mean score for students taught using conventional methods was 68.14. Prerequisite tests confirmed that the pretest and posttest data for both classes were normally distributed and homogeneous. Hypothesis testing using a t-test revealed a calculated t-value greater than the critical t-table value (4.069>1.668) at a 5% significance level (df=68). Consequently, H0 was rejected, and Ha was accepted, confirming that the problem-based learning model supported by interactive media has a significant effect on the physics learning outcomes of students at SMAN 1 Sambelia.